The initial U.S. experience with the Tempo active fixation temporary pacing lead in structural heart interventions. Issue 5 (2nd September 2019) - Nazif, Tamim M.; Chen, Shmuel; Codner, Pablo; Grossman, Paul M.; Menees, Daniel S.; Sanchez, Carlos E.; Yakubov, Steven J.; White, Jonathan; Kapadia, Samir; Whisenant, Brian K.; Forrest, John K.; Krishnaswamy, Amar; et al.
Abstract: Objectives: This multicenter retrospective study of the initial U.S. experience evaluated the safety and efficacy of temporary cardiac pacing with the Tempo® Temporary Pacing Lead. Background: Despite increasing use of temporary cardiac pacing with the rapid growth of structural heart procedures, temporary pacing leads have not significantly improved. The Tempo lead is a new temporary pacing lead with a soft tip intended to minimize the risk of perforation and a novel active fixation mechanism designed to enhance lead stability. Methods: Data from 269 consecutive structural heart procedures were collected. Outcomes included device safety (absence of clinically significant cardiac perforation, new pericardial effusion, or sustained ventricular arrhythmia) and efficacy (clinically acceptable pacing thresholds with successful pace capture throughout the index procedure). Postprocedure practices and sustained lead performance were also analyzed. Results: The Tempo lead was successfully positioned in the right ventricle and achieved pacing in 264 of 269 patients (98.1%). Two patients (0.8%) experienced loss of pace capture. Procedural mean pace capture threshold (PCT) was 0.7 ± 0.8 mA. There were no clinically significant perforations, pericardial effusions, or sustained device‐related arrhythmias. The Tempo lead was left in place postprocedure in 189 patients (71.6%) for mean duration of 43.3 ± 0.7 hr (range 2.5–221.3 hr) with final PCT of 0.84 ± 1.04 mA ( n = 80). Of these patients, 84.1% mobilized out of bed with no lead dislodgment. Conclusion: The Tempo lead is safe and effective for temporary cardiac pacing for structural heart procedures, provides stable peri and postprocedural pacing and allows mobilization of patients who require temporary pacing leads.